Biology and Management of Liverwort (Marchantia polymorpha) in Ornamental Crop Production - Stephen Christoper Marble; Marc S. Frank; Dail Dail Laughinghouse; Shawn T. Steed; Nathan S. Boyd (EDIS)
This article discusses management of liverwort in ornamental plant production. Liverwort is a unique weed species that poses special challenges for growers in terms of management. This article is the result of numerous consultations with FL growers seeking advice on management options for this species in nurseries, containers, and in greenhouses and other production areas.